2019
DOI: 10.1007/s00705-019-04178-0
|View full text |Cite
|
Sign up to set email alerts
|

Rescue and characterization of a recombinant HY12 bovine enterovirus carrying a foreign HA epitope in the 3A nonstructural protein

Abstract: Full-length infectious cDNA clones for recombinant HY12 bovine enteroviruses designated as rHY12-3A-2-HA, rHY12-3A-3-HA, and rHY12-3A-9-HA were constructed by the insertion of an epitope from influenza virus hemagglutinin (HA) at the N-terminus of the HY12-encoded 3A protein at amino acid positions 2, 3, and 9. The recombinant HY12 viruses expressing the HA epitope were rescued and characterized using immunoperoxidase monolayer assay, western blotting, and electron microscopy. The three rescued recombinant mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The BEV genome contains a large open reading frame encoding four structural proteins and seven nonstructural proteins. Previous studies explored various potential insertion sites for exogenous genes in BEV vectors, including the junction of the VP1 and 2A genes within the 2A, 2C, 3A, and VP1 genes, and in the VP1 B-C or D-E loop [15][16][17]. Early studies showed no adverse effects on viral biology or replication after insertion of exogenous epitopes at these sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BEV genome contains a large open reading frame encoding four structural proteins and seven nonstructural proteins. Previous studies explored various potential insertion sites for exogenous genes in BEV vectors, including the junction of the VP1 and 2A genes within the 2A, 2C, 3A, and VP1 genes, and in the VP1 B-C or D-E loop [15][16][17]. Early studies showed no adverse effects on viral biology or replication after insertion of exogenous epitopes at these sites.…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al [16] inserted the main antigen neutralization epitope (residues 141-160) of the FMDV (vaccine strain O1/Manisa/Turkey/69) VP1 gene into the junction of VP1/ 2A of BEV (LC-R4 strain). Liu et al [17] constructed a recombinant infectious BEV clone by insertion of the epitope of influenza virus hemagglutinin (HA) into the 3A or VP1 gene of BEV (HY12 strain), respectively. These studies indicated that the biological characteristics of recombinant BEV are similar to those of the parental virus, and experimental infection animal models could produce immune responses to the exogenous genes.…”
Section: Introductionmentioning
confidence: 99%